FRI0344 SEXUAL FUNCTION IN GERMAN WOMEN WITH SYSTEMIC SCLEROSIS COMPARED TO WOMEN WITH SYSTEMIC LUPUS ERYTHEMATODES AND EVALUATION OF A SCREENING TEST. (June 2019) - Schmalzing, Marc; Nau, Lena Friederike; Gernert, Michael; Schwaneck, Eva Christina; Saur, Sebastian; Tony, Hans-Peter; Henes, Melanie; Henes, Jörg
Abstract : Background: Few studies have been conducted to address the impact of systemic lupus erythematodes (SLE) or systemic sclerosis (SSc) on sexual function (1, 2), and so far none in Germany. Objectives: To assess and compare sexual dysfunction (SDF) in female patients with SLE or SSc, to correlate sexual function with disease characteristics and depression, and to evaluate a short questionnaire (Qualisex) as a screening test. Methods: Female patients with systemic lupus erythematodes or systemic sclerosis in two German tertiary university hospitals were evaluated with a self-designed questionnaire on various sexual and gynaecological aspects, a 19-item version of the Female Sexual Function Index (FSFI), the 9-item questionnaire Qualisex, and the Beck's depression inventory in a prospective study. Results: 171 female patients were included into the study. Among them 83 suffered from SSc (mean age 48.50 years), and 88 from SLE (mean age 39.65 years). Organ involvement and immunosuppressive medication was frequent in both groups. 34.9% of SSc patients and 28.4% of SLE patients ever received cyclophosphamide. Disease duration was significantly longer in SLE patients (13.17 vs 9.85 years in SSc patients, p=0.021). No significant differences between SSc and SLE were found as to educational background, BDI depression categories, marital status, or number of children. Only 9.6% of SSc patients and 14.8% of SLE patients had ever discussed sexual problems with their physician, whereas 52% of all patients thought that these were relevant in relation to their disease. Significantly more SSc patients would wish to discuss sexuality with their physician more intensively (37.3% vs 28.4% in SLE patients, p=0.011). 79.5% of SSc patients and 79.4% of SLE patients were in a constant relationship; 62.6% (52 of 83) of SSc patients and 67.0% (59 of 88) of SLE patients were sexually active. Impeding factors like vaginal stenosis, sicca, impaired mobility of pelvis, or pain did not differ significantly between SSc and SLE. Among the 51 sexually active and evaluable SSc patients a mean FSFI of 25.53 (±5.06) was found, with a FSFI value below the cut off defining SDF (<26.55) in 49% of patients, which did not differ significantly compared to SLE patients (n=59, mean FSFI 26.92 (±5.17), SDF in 45.8%). More patients who suffered from SDF had at least mild depression defined by BDI than patients without SDF (71.2% vs. 46.4%, p=0.016). SSc patients showed a numerically better Qualisex than SLE patients (2.98 (±2.24) vs. 3.16 (±2.45) with 0 meaning no impairment and 10 severe impairment). The Qualisex correlated significantly with the FSFI (r=-0.367; p<0.001) with numerically better correlation in SSc patients (r=-0.407, p=0.001 vs r=-0.340, p=0.004). Conclusion: Sexual Dysfunction (SDF) is a frequent problem in female patients with SSc and SLE. Frequency and nature are comparable between the two entities. Addressing sexual issues during medical consultation is an unmet need. The Qualisex constitutes a short questionnaire, which is suitable for SDF screening. References: [1] Rosato E, Rossi C, Molinaro I, Digiulio M, Trombetta A, Marra A, et al. Sexual distress, sexual dysfunction and relationship quality in women with systemic sclerosis: correlation with clinical variables. International journal of immunopathology and pharmacology. 2014;27(2):279-85. [2] Yin R, Xu B, Li L, Fu T, Zhang L, Zhang Q, Li X, Shen B. The impact of systemic lupus erythematosus on women's sexual functioning: A systematic review and meta-analysis. Medicine (Baltimore). 2017Jul;96(27):e7162. Disclosure of Interests: Marc Schmalzing Grant/research support from: Pfizer, Chugai, MSD, Janssen-Cilag, BMS, Celgene, UCB, Consultant for: Abbvie, Chugai, Genzyme, Hexal/Sandoz, MSD, Novartis, Roche, Sanofi Pasteur, Speakers bureau: Actelion, Baxalta/Shire, BMS, Celgene, Chugai, Janssen-Cilag, MSD, Novartis, Pfizer, Roche, UCB, Lena Friederike Nau: None declared, Michael Gernert: None declared, Eva Christina Schwaneck: None declared, Sebastian Saur : None declared, Hans-Peter Tony Consultant for: Eli Lilly and Company, Speakers bureau: Eli Lilly and Company, Melanie Henes: None declared, Jörg Henes: None declared